Elaboración de láminas biodegradables a partir de los residuos del almidón de yuca(Manihot esculenta) - Menoscal Chichanda, Richard Esteven (2017)
This research aimed at developing biodegradable sheets from the residues of cassava (Manihot esculenta) starch as an alternative to reduce contamination caused by non-biodegradable residues, as an alternative to using common plastic. The selection of the raw material to be used and its proportions were stablished; due to its availability, cassava starch was used in the highest proportion (80%, 50%, 30%); in addition, water, glycerin and vinegar were used as plasticizers, because of the additional properties that they provide to the plastic. The materials formed 3 mixtures in w/w ratio; 80% starch + 13% water + 0.3% acetic acid + 6.7 glycerin; 50% starch + 42% water + 0.4% acetic acid + 7.6 glycerin; and 30% starch + 5% acetic acid + 8.5 glycerin, each mixture was blended, heated (between 60°C and 67°C) and poured into molds, 6 experimental units of 100g for each mixture were prepared, forming 18 sheets of 15x10 cm. 9 sheets were buried and 9 were left outdoor for 90 days, monitoring was done twice a week until reaching at least 90% of degradation. Treatment 1 which used the highest proportion of raw material (80%) showed the highest degradation time 90.67 ± 0.58 and 59.67 ± 1.53 days outdoor and buried respectively, with a cost of $ 2.82 per sheet.